Compression and communication in the cultural evolution of linguistic structure - Kirby, Simon; Tamariz, Monica; Cornish, Hannah; Smith, Kenny (Cognition, 2015)
•We provide a cultural evolutionary account of the origins of linguistic structure.•Cultural evolution delivers a trade-off between compressibility and expressivity.•A compression pressure arises when naive learners influence language evolution.•An expressivity pressure arises due to the use of language for communication.•The basic design features of language are a response to these competing pressures. Language exhibits striking systematic structure. Words are composed of combinations of reusable sounds, and those words in turn are combined to form complex sentences. These properties make language unique among natural communication systems and enable our species to convey an open-ended set of messages. We provide a cultural evolutionary account of the origins of this structure. We show, using simulations of rational learners and laboratory experiments, that structure arises from a trade-off between pressures for compressibility (imposed during learning) and expressivity (imposed during communication). We further demonstrate that the relative strength of these two pressures can be varied in different social contexts, leading to novel predictions about the emergence of structured behaviour in the wild.